Correlation of maternal serum bile acid induced placental inflammation by Gpbar-1 and NF-κB pathway with fetal outcome in intrahepatic cholestasis of pregnancy: a case control study - Singh, Alpana; Sharma, Shivani; Batra, Prerna; Banerjee, B. D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Intrahepatic cholestasis of pregnancy (IHCP) is a pregnancy-specific liver disorder associated with adverse fetal outcomes. Elevated maternal serum bile acids (BAs) trigger placental inflammation through the G-protein-coupled bile acid receptor 1 (Gpbar-1) and nuclear factor Kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway. This study investigates Gpbar-1 and NF-κB gene expression in placental tissue of IHCP patients and its correlation with fetal outcomes. Methods: This prospective case-control study, conducted between November 2019 and October 2021 at a tertiary care hospital, included 30 diagnosed IHCP cases and 30 gestational age-matched healthy controls. Serum bile acid levels were measured (using Elisa), and placental tissue was analyzed post-delivery using quantitative reverse transcription PCR (RT-qPCR) for Gpbar-1 and NF-κB gene expression. Maternal and fetal outcomes such as preterm delivery, fetal distress, low APGAR score, meconium-stained liquor, and NICU admission were recorded. Results: Serum bile acid levels were significantly higher in IHCP cases (p<0.001). Gene expression analysis showed a 2.192-fold upregulation of Gpbar-1 (p=0.019) and a 2.396 -fold upregulation of NF-κB in IHCP placentas (p=0.029). Adverse fetal outcomes were not significantly correlated with higher gene expression. Conclusions: Elevated bile acid levels in IHCP activate the Gpbar-1/NF-κB pathway, leading to placental inflammation and adverse fetal outcomes. Targeting this pathway may improve pregnancy outcomes in IHCP. Further research on anti-inflammatory therapies is recommended.